STATUS OF FALL ARMYWORM SPODOPTERA FRUGIPERDA (J.E. SMITH) IN SUGARCANE IN TAMIL NADU STATE, INDIA, A YEAR AFTER ITS FIRST OCCURRENCE - Srikanth, Jandhyala; Geetha, N; Mahesh, P; Saravanan, L; Singaravelu, B; Salin, K P (Journal of Sugarcane Research, 2020)
The status of fall armyworm (FAW) Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) on sugarcane in Tamil Nadu State, India, in the past one year, i.e. since its first occurrence on the crop in November 2018, is presented in this communication with comparative observations in maize. In M/s Bannari Amman Sugars Ltd, Sathyamangalam, attack rates in young sugarcane (cv Co 14061) crop were lower (0.0- 7.2%) than in maize (86.4%). In M/s Amaravathi Sugars, Udumalpet, too, sugarcane (cv Co 86032) recorded lower (1.7%) attack rates than maize (33.8%). The incidence level in M/s Sakthi Sugars, Appakudal, was about 20.0%. In experimental plots, the attack rates in diverse germplasm, including commercial hybrids, was less than 2.2%. Selected life-history parameters such as percent of pupation, percent of adult emergence and sex ratio recorded in small field-collected samples were more or less same in sugarcane and maize. Likewise, pupal period and pupal weight of males and females did not differ significantly between the two hosts. The entomopathogenic fungus Metarrhizium (=Nomuraea) rileyi (Farl.) Kepler, Rehner & Humber was observed in FAW larvae collected from maize and not sugarcane. The host preference displayed by FAW and M. rileyi was discussed in relation to the long-term occurrence of the former and biological control prospects with the latter.